Academic Senate Minutes 2007-02-08 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 11/9; 11/30 & 12/14 approved. Faculty Eligible for Emeritus Status Spring 2007: Manual Hidalgo, CALS approved. End of Year report from the Professional Development subcommittee. AMCS curriculum revision approved. Provost Report. EPC resolution re: Admissions of Unclassified Graduates postponed to next meeting. Discussion of impaction and related admissions issues postponed to next meeting. Student Presentation on anti-war activities. Motion that the Academic Senate urge the university administration and faculty to make every reasonable accommodation to facilitate the political expression students intend to make February 12-15th. approved. Resolution in Support of the California Faculty Association in Bargaining with the CSU approved. Chair Elect report. Statewide Senator report.